2022
DOI: 10.1021/acsomega.1c06741
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid Biosurfactants for Oil Recovery: Salt Effects on the Structural Properties Investigated by Mesoscale Simulations

Abstract: Rhamnolipids (RLs) are biosurfactants produced by Pseudomonas. The biodegradability and the variety of their functionality make them suitable for environmental remediation and oil recovery. We use dissipative particle dynamics simulations to investigate the aggregation behaviors of ionic RL congeners with nonane in various operating conditions. Under zero-salinity conditions, all RL congeners studied here form small ellipsoidal clusters with detectable free surfactants. When salt ions are present, the electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Lipopeptides exhibit strong surface activity, foam-forming capability, and suitable stability. Surfactin, produced by Bacillus subtilis , is a well-known lipopeptide used in EOR due to its emulsification properties and ability to reduce interfacial tension [ 92 ]. Lichenysin produced by Bacillus licheniformis is also another example of this class of microbial biosurfactant [ 54 ].…”
Section: Biosurfactants: Nature Properties and Their Applications To Eormentioning
confidence: 99%
“…Lipopeptides exhibit strong surface activity, foam-forming capability, and suitable stability. Surfactin, produced by Bacillus subtilis , is a well-known lipopeptide used in EOR due to its emulsification properties and ability to reduce interfacial tension [ 92 ]. Lichenysin produced by Bacillus licheniformis is also another example of this class of microbial biosurfactant [ 54 ].…”
Section: Biosurfactants: Nature Properties and Their Applications To Eormentioning
confidence: 99%
“…Moreover, integrating such meta-analysis data with application-specific data could potentially serve as a tool for producing surfactants with tailored properties. While there are examples of applying chemometric tools in RL research, they mainly focus on optimizing BS production efficiency 26 28 , aggregation behavior 29 , solubilization and biodegradation of PAHs 30 , treatment of oily sludges 31 , 32 , coal recovery 33 , and selected adsorption characteristics 34 . To our knowledge, attempts of developing guidelines for the biosynthesis of BSs with specified and targeted properties have not been reported in the scientific literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnolipids are a type of glycolipid that can be biologically produced by Pseudomonas species . As a well-known biosurfactant, rhamnolipids are biodegradable and relatively nontoxic , and therefore have been studied and applied to a variety of industrial and environmental uses. , Also, numerous studies have been carried out to investigate the structures and morphologies of rhamnolipids, especially computationally, at both vacuum–water ,, and oil–water interfaces, and in rhamnolipid mixtures and solutions. It was found that the conformations, interactions, and self-assembly structures can be greatly affected by salinity, ionization, and alkyl chain lengths.…”
Section: Introductionmentioning
confidence: 99%